2019
DOI: 10.1253/circrep.cr-19-0074
|View full text |Cite
|
Sign up to set email alerts
|

MitraClip in Asia ― Current Adoption and Regional Data ―

Abstract: almost all Asian countries (except Japan) affects the rate of uptake. Second, regulatory approvals take time and effort to obtain. Furthermore, some countries such as Japan and China require local trials before approval for use. Third, the conservative nature of Asian societies, both patients and physicians, may make adoption of relatively newer technologies a slower process. The first MitraClip procedure in the Asia-Pacific was performed at Sir Charles Gairdner Hospital, Australia, on 23 March 2011, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…SEA indicates Southeast Asia (Singapore, Malaysia, Indonesia, Brunei, Philippines, Vietnam, Thailand). Source: Data derived from Wong et al 92…”
Section: Valvular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…SEA indicates Southeast Asia (Singapore, Malaysia, Indonesia, Brunei, Philippines, Vietnam, Thailand). Source: Data derived from Wong et al 92…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…Use of MitraClip procedures has also increased in Asia, although at a slower pace (Chart 23-2), with the highest increase seen in Japan from 18 procedures in 2011 to 439 procedures in 2018. 92…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…Use of MitraClip procedures has also increased in Asia, although at a slower pace (Chart 23-4), with the highest increase seen in Japan from 18 procedures in 2011 to 439 procedures in 2018. 112…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…Surgical mitral valve repair or replacement is still the gold standard for DMR, although transcatheter therapy may have a role in the management of a subset of patients. [ 7 , 8 , 14 , 15 ] Data from MARS found that the acute procedural success rate for patients with DMR was 92%. [ 3 ] The 30-day major adverse event rate was 14.7%, which was not significantly different from FMR patients (9.2%; p=0.555).…”
Section: Mitraclip Use In Degenerative Mitral Regurgitationmentioning
confidence: 99%
“…However, published data on the use of the MitraClip among Asian populations are limited compared with the West. [ 7 ] The multicentre retrospective MARS registry, involving eight sites in five Asia-Pacific countries, reported the early experience in Asia with 142 patients who underwent the MitraClip procedure from February 2011 to October 2013. In this study, the acute procedural success rate was 93.7%.…”
mentioning
confidence: 99%